2011
DOI: 10.1007/s13148-011-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of mucin genes in human cancers

Abstract: Mucins are high molecular weight glycoproteins that play important roles in diagnostic and prognostic prediction and in carcinogenesis and tumor invasion. Regulation of expression of mucin genes has been studied extensively, and signaling pathways, transcriptional regulators, and epigenetic modification in promoter regions have been described. Detection of the epigenetic status of cancer-related mucin genes is important for early diagnosis of cancer and for monitoring of tumor behavior and response to targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 126 publications
1
42
0
Order By: Relevance
“…It has been shown previously that expression of mucin genes such as MUC1 , MUC2 , MUC3 , MUC4, and MUC5AC are regulated by DNA methylation (5mC) of these promoter regions [1517]. Our results are the first to demonstrate that TET1-mediated DNA hypomethylation regulates the expression of MUC4 in lung adenocarcinomas.…”
Section: Discussionsupporting
confidence: 67%
“…It has been shown previously that expression of mucin genes such as MUC1 , MUC2 , MUC3 , MUC4, and MUC5AC are regulated by DNA methylation (5mC) of these promoter regions [1517]. Our results are the first to demonstrate that TET1-mediated DNA hypomethylation regulates the expression of MUC4 in lung adenocarcinomas.…”
Section: Discussionsupporting
confidence: 67%
“…In normal cells including human lung and gastric epithelial cells, macrophages and mouse placenta, MUC1 transcription is under the control of several transcription factors such as NF-κB, STAT3, HIF-1, SP1 and PPAR-γ (21,34,(43)(44)(45). In addition, epigenetic regulation including demethylation of the MUC1 promoter, and histone H3-K9 demethylation and acetylation are involved (46). Furthermore, suppressing micro-RNA-mediated downregulation of MUC1 expression was recently reported (25,36,37).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is very important to establish new diagnostic, prognostic and therapeutic biomarkers. It has been shown previously that expression of mucin genes (including MUC1 , MUC2 , MUC3 , MUC4 and MUC5AC ) is regulated by DNA methylation at promoter regions in cancer cell lines [1820, 35, 36]. In the present study, we analyzed the relationships among the expression of two mucins, MUC1 and MUC4 , their DNA methylation status at promoter regions, and expression of DNA methylation-related enzymes in pancreatic tissue in non-neoplastic and PDAC samples.…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 and MUC4 are often overexpressed in epithelial cancers, and our immunohistochemical studies in the pancreas and/or biomolecular studies have shown the following: (1) aberrant expression of MUC1 and MUC4 are associated with invasive proliferation of tumors and a poor outcome for patients [16, 17]; and (2) the expression of MUC1 / MUC4 mRNA is regulated by epigenetic mechanisms such as DNA methylation in the promoter region [1820]. …”
Section: Introductionmentioning
confidence: 99%